Feasibility of Android-Based Application SCIQU (Science in Al-Quran) as Science Learning Media for Madrasah Ibtidaiyah (MI) - Muttakin Muttakin; Zainul Mujtahid; Amam Taufiq Hidayat; Munzir Absa; Thalitha Attahara; Rahmah Nursada (Postgraduate, University of Mataram, 2023)
In this age of technological advancement, the process of learning in the classroom is required to be more adaptive, using various media that can enhance it. One of the learning media that can increase studentâ€™s interest is picture story media (comics). In this study, an android-based comic media was developed, called Science in Al-Qur'an (SCIQU), with material about clean and healthy lifestyles for grade V Madrasah Ibtidaiyah (MI) students. The media was developed using Research and Development (R & D) Method with ADDIE (Analyze, Design, Develop, Implement, Evaluate) Model. Â The media developed and the material presented in the media were validated by media expert validators and material experts. From the validation results, it was found that the media developed fell into the